OPTIMASI METODE ISOLASI DNA GENOM PADA TANAMAN KAPULASAN - Ediwirman Ediwirman; Ellina Mansya (Jurnal Agroekoteknologi, 2009)
ABSTRACTHigh quality and quantity of genomic DNA for plant kapulasan is required for analyses based on the polymorfisme chain reaction (PCR) technic.  Method DNA isolation were proven to be genus or even species spesific. Objective of this study was to determine of methode with using protocol most reliably produced sufficient quantity and good quality of plant kapulasan genomic DNA.  Method utilizing Doyle and Sanghai-Maroof with storge of leaf until dry, yielded higher quality and quantity of genomic DNA.Key words : DNA,  Kapulasan